ChemInform Abstract: An Explanation of the Mechanism for Laser Induced Selective Activation Using Diffusion Theory. Issue 16 (22nd April 2014) - Zhang, Yang; Norgaard, Hansen Hans; Henri, Hattel Jesper; Tang, Peter Torben; Skov, Nielsen Jakob; Celal, Tutum Cem
Abstract Review: 13 refs.